2012
DOI: 10.1039/c1nr11073j
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and properties of aromatic amino acids on single-walled carbon nanotubes

Abstract: We investigated the adsorption of three aromatic amino acids-phenylalanine, tyrosine, and tryptophan-on the sidewalls of a number of representative single-walled carbon nanotubes (SWNTs) using density-functional tight-binding calculations, complemented by an empirical dispersion correction. The armchair (n, n) SWNTs (n = 3-12) and zigzag (n, 0) SWNTs (n = 4-12) were thoroughly examined. We found that the most stable amino acid/SWNT complexes for different SWNTs have similar local structures, and that the dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 29 publications
9
43
0
Order By: Relevance
“…In our work, we use larger water clusters (H 2 O) 40 , (H 2 O) 48 , and (H 2 O) 56 to simulate n-gonal ice nanotubes (INTs, n = 5-7). By employing the SCC-DFTB-D method, we investigate the energies, geometry structures, and IR and resonant Raman spectra of INTs confined in SWCNTs.…”
Section: Ice Nanotubes (Ints) Confined In Swcntsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our work, we use larger water clusters (H 2 O) 40 , (H 2 O) 48 , and (H 2 O) 56 to simulate n-gonal ice nanotubes (INTs, n = 5-7). By employing the SCC-DFTB-D method, we investigate the energies, geometry structures, and IR and resonant Raman spectra of INTs confined in SWCNTs.…”
Section: Ice Nanotubes (Ints) Confined In Swcntsmentioning
confidence: 99%
“…The SCC-DFTB-D approach has been successfully applied to investigate the energies and structures of some weakly bonded systems [9,11,12,[37][38][39][40][41].…”
Section: Theorymentioning
confidence: 99%
“…48 Through combined Monte Carlo modeling and in vitro selection techniques such as phage display, Wang et al 49 engineered polypeptides capable of recognizing the surface of SWCNTs using consensus binding sequences containing motifs rich in aromatic side chains at specific locations. By investigating the adsorption of aromatic amino acids Phe, Tyr, and Trp onto the SWCNT surface, Wang and co-workers 50 identified π−π stacking interactions between the benzene (Phe and Tyr) and indole (Trp) rings of the residues and carbon nanotubes as key interactions in the adsorption process (Figure 2). Of the aromatic residues, Trp and Phe were shown to have the highest and lowest binding affinities toward carbon nanotubes, respectively.…”
Section: Nonspecific Protein and Peptide Adsorptionmentioning
confidence: 99%
“…Furthermore, increasing contact area by, for example, increasing the diameter or length of the SWCNT enhances the adsorption energy. 50 Density functional theory (DFT) and Møller−Plesset secondorder perturbation theory (MP2) calculations have shown that the most preferable geometrical orientation for all aromatic rings is parallel to planar graphene sheets with distances around 3.21, 3.33, 3.34, and 3.50 Å for His, Phe, Tyr, and Trp rings, respectively. 59 Overall, the interaction between the amino acids and graphene was found to be stronger than that for SWCNTs, suggesting that increased curvature disrupts the binding interaction.…”
Section: Nonspecific Protein and Peptide Adsorptionmentioning
confidence: 99%
“…To this end, two amino acids, Lcysteine and L-glutamic acid were used. Hybrid materials containing amino acids can be used as adsorbents of pollutants (Deng et al, 2012;Gondikas et al, 2012;Liu et al, 2014;Zhang et al, 2014;Choi et al, 2015), additives to polymers (Mallakpour and Dinari, 2013;Kausar, 2014), catalysts (Zamani and Izadi, 2013;, and for various biomedical applications (Wang et al, 2012;Dragneva et al, 2013;Songurtekin et al, 2013). Determination of cation-exchange capacity (CEC) and specific surface area, FTIR spectroscopy, X-ray diffraction analysis and determination of C content were used for the characterization of the prepared samples.…”
Section: Introductionmentioning
confidence: 99%